1990
DOI: 10.1213/00000539-199005000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nifedipine on Morphine-Induced Analgesia

Abstract: Experimental data show that opiates interfere with calcium influx in the cell and that some calcium-channel blockers are analgesic. We therefore studied the effect of the calcium-receptor blocker nifedipine on the analgesic effect of morphine in the rat, using tail-flick responses, and in humans, using measurements of the intensity of postoperative pain. In both the experimental animals and humans nifedipine significantly (P less than 0.001) increased the analgesic effect of morphine independently of any effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…In particular, the extracellular calcium influx and release from stores were larger in IL‐6 treated neurons compared with controls. Since it has been demonstrated that morphine exerts an inhibitory effect on cellular calcium (North 1986) and that calcium plays an important role in modulating the analgesic effect of morphine in both experimental animals and humans (Carta et al . 1990; Kuzmin et al .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the extracellular calcium influx and release from stores were larger in IL‐6 treated neurons compared with controls. Since it has been demonstrated that morphine exerts an inhibitory effect on cellular calcium (North 1986) and that calcium plays an important role in modulating the analgesic effect of morphine in both experimental animals and humans (Carta et al . 1990; Kuzmin et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, the on-demand iv infusion of fentanyl for the control of pain after elective hysterectomy was not significantly different in groups of patients double-blindly assigned to the administration of an additional infusion of either placebo or nimodipine (51). Oral administration of slow-release tablets of nifedipine given 18, 9 and 1 h before the beginning of surgery significantly potentiated the analgesic effect of morphine slowly infused by the iv route in patients submitted to elective hysterectomy or orthopedic surgery (30). However, slow-release nifedipine given orally 12 and 1 h before surgery did not change significantly the postoperative pain relief produced by epidural fentanyl (52).…”
Section: Clinical Studiesmentioning
confidence: 98%
“…[10] In the study by Carta et al, a slow release preparation of nifedipine was used (half-life of 15.2 ± 4.3 h), which might have delayed its antianalgesic action. [11]…”
Section: Discussionmentioning
confidence: 99%